Insulin resistance in the horse: a review. Issue 1 (1st January 2016) - Kaczmarek, Katarzyna; Janicki, Bogdan; Głowska, Maria
ABSTRACT: Insulin resistance (IR) is a state in which the tissues show a reduced sensitivity to insulin despite its normal or even increased concentration in blood. IR causes inability of peripheral tissues to respond to the hormone and to increase the glucose uptake from blood nor to raise the metabolism rate. The tissues resistance to insulin may refer to the prereceptor malfunctions, which reduce the concentration of insulin or decrease the number of insulin receptors; however, in most cases changes in signal transduction after insulin binding to the receptor are observed. The development of IR is determined by a number of genetic and environmental factors. One of the most relevant causes is obesity, which develops into a growing problem among the horse population all over the world. The accumulation of lipids in the tissues (lipotoxicity) and a mild inflammation caused by the release of proinflammatory adipokines and cytokines from the fat tissue are a common denominator that links obesity with IR. Both IR and obesity seem to cause metabolism malfunctions in horses and are the key components of equine metabolic syndrome; moreover, both may be the reason for endocrinological laminitis. The methods of prevention and treatment of IR include feeding the animals with low glycemic index food and increasing physical activity as well as pharmacological treatment, where levothyroxine sodium and metformin are of the highest importance.